Neuroprotection by dihydrotestosterone in LPS-induced neuroinflammation - Yang, Lei; Zhou, Renyuan; Tong, Yu; Chen, Pengfei; Shen, Yu; Miao, Shuai; Liu, Xiaoqiang (Neurobiology of disease, 2020)
Microglia-induced neuroinflammation plays a vital role in the etiology and progression of neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease and multiple sclerosis. The neuroprotective role of androgens, including testosterone and its metabolite dihydrotestosterone (DHT), has been increasingly demonstrated in these diseases, but few studies investigated the effects of androgen on neuroinflammation. This study investigated the role of DHT in lipopolysaccharide (LPS)-induced neuroinflammation, neuronal damage and behavioral dysfunction, as well as underlying mechanisms. We showed that DHT inhibited LPS-induced release of proinflammatory factors, including TNF-α, IL-1β, IL-6; iNOS, COX-2, NO, and PGE2 in BV2 cells and primary microglia by suppressing the TLR4-mediated NF-κB and MAPK p38 signaling pathways, thus protecting SH-SY5Y neurons from inflammatory damage induced by activated microglia. In an LPS-induced neuroinflammation mouse model, endogenous DHT depletion by castration exacerbated inflammatory responses by upregulating the levels of TNF-α, IL-1β, IL-6, iNOS, and COX-2 in the serum and brain by increasing the LR4-mediated NF-κB and MAPK pathway activation, but these effects were restored by exogenous DHT supplementation. Moreover, DHT also regulated the mRNA levels of the anti-inflammatory cytokines IL-10 and IL-13 in the brain. In addition, DHT modulated the expression of Aβ, the apoptotic proteins caspase-3, Bcl-2, and Bax, and synaptophysin, as well as neuronal damage in LPS-treated mouse brains. Further behavioral tests revealed that DHT ameliorated LPS-induced spatial and learning impairment and motor incoordination, and partly improved the locomotor activity in LPS-injected mice. Therefore, this study suggests that DHT exerts anti-neuroinflammatory and neuroprotective effects; thus, androgen replacement therapy is a potential therapeutic strategy for improving cognitive and behavioral function in neuroinflammation-related diseases.